Kideogames: Reimagining the Fringe of Literary Studies as the Forefront. Issue 7 (22nd April 2019) - Reay, Emma
The absence of children's texts and ludic texts from traditional literary canons, curricula, journals, and conferences might appear obvious, practical, and natural—a straightforward reflection of theoretical and methodological divergence, and of the way texts are grouped outside of academic study. However, these seemingly self-evident explanations do not hold up under scrutiny. In this article, I posit that the omission of children's texts and ludic texts from well-developed scholarly contexts is partly rooted in the ideological collocation of "children, " "play, " and "low culture." I compare the strategies used by children's literature studies and games studies to manage their marginalization and conclude that irrespective of the quality, the variety, the relevance, and the impact of research conducted within these two disciplines, neither will find a permanent home in the serious, sophisticated, "adults-only" space of the literature faculty. I ask whether this is necessarily a problem, and suggest that - when consciously embraced - the lightness of illegitimacy may be a potent as the heft of tradition. Finally, I advocate for an intersectional alliance between children's literature studies and games studies and explore some of the ways in which this kind of academic solidarity might counter the marginalizing effects of infantilization.